The influences of mental toughness and skill undergoing the rehabilitation program / Tasyleem A Latif - A Latif, Tasyleem (Faculty of Sport Science and Recreation, 2018)
The investigation of mental toughness and skill focused undergoing rehabilitation program still in open question. The problem of drop-out patients in rehabilitation program cannot be solved by increase the intensity of the exercise, but psychological state must be improved as well. The aim of this research was to identify factor influences of mental toughness and skill undergoing the rehabilitation program. In addition, forty patients (N=40) from Shah Alam Physiotherapy Center involved in this research. This research is based on data obtained from Mental Toughness Questionnaires 48-item (MTQ48) by Clough, Earle and Sewell (2002) and Bull's Mental Skill Questionnaires (1996) that collected the mental toughness and skill state between patients undergoing rehabilitation program. The data were analysed to evaluate and determine the main outcome in MTQ48 and influences of mental skill undergoing rehabilitation program. The results of the study also suggested that outcome of MTQ48 influenced in male (511.14 ± 44.61), age 19-25 (507.69 ± 35.22), three to six weeks duration of the injury (524.5 ± 38.73), four to five times per week sport or physical activity (517.73 ± 37.46) , above six years of sport experiences (607 ± 36.45) and normal in Body Mass Index (BMI) status (507.07 ± 26.87). MQS also was involved in the rehabilitation program which is imagery abilities (51.25 ± 3.43), mental preparation (57.28 ± 4.79), concentration (34.23 ± 7.42), self-confidence (45.05 ± 4.36), anxiety and worry management (38.33 ± 6.5), motivation (58.98 ± 3.06) and relaxation (48.38 ± 3.36). In conclusion, there are influences in mental toughness and skill in the rehabilitation program. Suggestion of this research, mental skill training may improve the mental toughness patients to encounter the stressful environment. Therefore, patients able to commitment toward the program and reduce the severity and period of recovery.